Vibration signal model of an aero-engine rotor-casing system with a transfer path effect and rubbing. (July 2019) - Hou, Lanlan; Cao, Shuqian; Gao, Tian; Wang, Shiyu
Highlights: Multi-paths modulate vibration transfer signals of aero-engine rotor-casing system. Combination of bearing varying compliance frequencies and rotor frequency features. Rubbing brings a new vibration transfer path and reduces amplitude of vibrations. Abstract: This paper addresses modeling of vibration signals produced by rotor-localized excitation and modulated by multi-paths in an aero-engine rotor-casing system. The aim is to provide a better understanding of specific features of measurement point signals at the casing. Multi-paths effects are incorporated, including rubbing and rotor-casing paths through backup and inter-shaft bearings. The vibration waveforms and spectral signatures of signals with and without rubbing are derived and simulated. The most critical features of the resulting vibration signal are a prominent double rotating frequency and smaller overall amplitudes of frequencies due to rubbing, and bearing varying compliance (VC) frequencies due to the rotor-casing paths. A novel pneumatic-driven dual-rotor-casing test bench with a pneumatic rubbing structure is designed to initiate rubbing and acquire vibration signals at the casing. The test results provide sound verification for the proposed signal models. The analysis may prove useful for simulation purposes and rubbing fault diagnosis.